Formulasi Dan Evaluasi Mutu Fisik Granul Ekstrak Etanol Kunyit Putih (Curcuma zedoaria) Dengan Variasi Konsentrasi Bahan Pengikat Polivinil Pirolidon - Apriliani, Wayan; Juliadi, Debby; Suradnyana, I Gede Made (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
White turmeric (Curcuma zedoaria) is a medicinal plant that Indonesian people widely use as a treatment for a disease. This plant is processed by blending it and serving it as a traditional medicine. However, the method of processing which is still very traditional allows errors in processing to make the efficacy of white turmeric not optimal, besides that the preparations that are processed cannot be used for a long time. Granule is a solid dosage form intended for oral use, the advantage of this preparation is the flexible dosage weight which allows for the formulation of large amounts of active ingredients such as most extracts. This study aims to obtain white turmeric ethanol extract granules with varying concentrations of polyvinyl pyrrolidone, namely 1%, 3%, and 5% which have good physical quality. The test results from this study showed that the physical quality of the preparation was good, in which the organoleptic preparation obtained was light yellow, smelled of orange aroma, and granular form. The granule compressibility test of the three formulas complied with the requirements because it was <20%. The granule flow rate test showed that the three formulas met the requirements, namely >10 gram/second. Test angle of repose of the three formula granules meet the requirements> 40o. The granule soluble time test showed that the three formulas met the requirements, namely <5 minutes and the granule water content test of the three formulas met the requirements, namely <5%. Polyvinyl pyrrolidone (PVP) binders with concentrations of 1%, 3%, and 5% produced good granules.